Association Between HIV/AIDS Knowledge and Sexual Activity Behavior Among Indonesian Couples Aged 20 to 40: A Cross-Sectional Study - Niniek Budiarti Burhan; Jerry Reyhan Wardanna; Ayunda Dewi Jayanti Jilan Putri; Dicky Faizal Irnandi (Indonesian Andrology and Biomedical Journal, 2024)
Background : In Indonesia, the escalating prevalence of STDs and HIV/AIDS poses a significant health challenge. The transmission of HIV occurs through various modes, including unsafe sexual behaviors and mother-to-baby transmission. Insufficient knowledge regarding STDs and sexual education contributes to the rising of HIV/AIDS cases. Objective : To investigate the relationship between knowledge of HIV/AIDS and sexual activity behavior among couples aged 20 to 40 in Indonesia. Methods : A cross-sectional study involving 384 Indonesian couples was conducted using a causal associative technique. Purposive sampling was employed to select participants aged 20 to 40, familiar with STDs, engaged in various relationship statuses (dating, married, or in a relationship without formal status), and willing to complete the questionnaire. The variables used to quantify respondents' knowledge levels included understanding of HIV/AIDS, HIV/AIDS transmission, and HIV/AIDS prevention and treatment. The variable measuring couples' sexual activity pertained to their involvement in HIV/AIDS preventive activities. Results : Analysis of the data revealed that 282 respondents (73.4%) demonstrated good knowledge, 73 respondents (19%) exhibited moderate knowledge, and 29 respondents (7.6%) displayed poor knowledge regarding HIV/AIDS. Among the participants, 202 respondents (52.6%) expressed support for safe sex, indicating engagement in HIV/AIDS preventive activities, while 182 others (47.4%) did not. T-test results for the variables of HIV/AIDS understanding, transmission, prevention, and treatment yielded values of 0.259 (>0.05), 0.259 (>0.05), 0.264 (>0.05), and 0.522 (>0.05) for the F-test. Conclusion : The study concludes that couples' knowledge of HIV/AIDS does not exert a significant influence on their sexual activity behavior.